Electrical Conductance Study of Aspartic Acid (Asp) Complex Cobalt (Co ΙΙ ) in Different Solvents and Temperatures - Hala A. Abedel – Rahman Associate; Yaman , Q. Sa'dullah; Rawya Z. Saeed (Tikrit Journal of Pure Science)
The electrical conductivities of Co(II) complex with aspartic acid (Asp) in different solvents (water, methanol and ethanol) at different temperatures were measured by assisting of  lee-Wheaton equation at the best fit values of standard deviled for analyzing the data of unsymmetrical electrolytes including,the conductivity parameters, the ionic conductivity M+2, the association constant KA, and the distance parameter R .